1987 November - ECOWAS (ECOWAS, 1987)
ECONOMIC COMMUNITY OF WEST AFRICAN STATES, 22ND SESSION OF THE COUNCIL OF MINISTERS LAGOS, 26 -28 NOVEMBER 1987
Council of Ministers 26 - 28 November 1987
Keywords: Council of Ministers 26 - 28 November 1987